Lesion Recognition and Cleavage of Damage-Containing Quadruplexes and Bulged Structures by DNA Glycosylases - Kuznetsova, Alexandra A.; Fedorova, Olga S.; Kuznetsov, Nikita A. (Frontiers in Cell and Developmental Biology, 2020)
Human telomeres contain the repeated TTAGGG sequence, in which the 3′-exposed strand may adopt a noncanonical G-quadruplex (Q4) structure. In addition, more than 40% of human genes have been found to contain (near the promoter regions) at least one such sequence that may form a quadruplex. The guanine-rich regions of telomeres are hotspots for oxidation forming 7,8-dihydro-8-oxoguanine, thymine glycol, and abasic sites (apurinic/apyrimidinic sites): the lesions that are handled by the base excision repair pathway. DNA glycosylases are key participants of base excision repair. Such an enzyme recognizes a damaged DNA base and catalyzes its excision. Other noncanonical DNA structures comprising bulges, hairpins, or bubbles may have a functionally important role. Nonetheless, the features of DNA repair processes in noncanonical DNA structures are still poorly understood. Therefore, in this work, a comparative analysis of the efficiency of the removal of a damaged nucleotide from various G-quadruplexes and bulged structures was performed using human 8-oxoguanine-DNA glycosylase (OGG1), endonuclease VIII-like 1 (NEIL1), and endonuclease III (NTH1). They are responsible for the repair of oxidative DNA lesions but belong to different structural families. The activities of prokaryotic formamidopyrimidine-DNA glycosylase (Fpg) and endonuclease VIII (Nei) were also analyzed. The stages of formation of enzyme–substrate complexes and catalysis were analyzed via pre–steady-state stopped-flow kinetics, which allow to register conformational rearrangements of model DNA substrates in the course of interaction with an enzyme. The obtained data indicate that the ability to recognize a specific lesion in the noncanonical structures by the DNA glycosylases does not depend on substrate specificity of the enzyme but clearly depends on their structural family.